Sources and methods of phosphorus application in maize cultivation - Pizzatto, Idianara Fernanda; Modolo, Alcir Jose; Campos, Jose Ricardo da Rocha; Sartor, Laercio Ricardo; Daniel, Diego Fernando; Dalbianco, Alessandro Bandeira [UNESP]; Dallacort, Rivanildo (Univ Federal Ceara, Dept Geol, 2025)
Despite having a vast area for agricultural production, Brazil is highly dependent on mineral sources for phosphate fertilisers, making their use unsustainable and highly dependent on the international market. The aim of the present study was to evaluate the effect of different sources of phosphate fertiliser and the depth of application on the development and productivity of maize over two crop seasons. A randomised block design was used in a 3 x 4 factorial scheme comprising 12 treatments, with four replications. Three sources of phosphorus were tested: single superphosphate (SSP), Top-Phos (R) (TOP-PHOS) and reactive natural phosphate (RNP), in addition to four methods of application (broadcast application [0.00 m] and in-furrow application at three depths [0.05 m, 0.08 m and 0.11 m]). The following parameters were evaluated: final plant stand, plant height, stalk diameter, ear insertion height, number of rows per ear, number of grains per row, 1000-grain weight, and grain productivity. The data were submitted to analysis of variance using the F-test at a level of 5%, and to principal component analysis (PCA) with biplot graphical analysis. The use of SSP and Top-Phos (R) increased productivity and the ear insertion height compared to the use of RNP. Applications made at a depth of 0.11 m were the most efficient. Seasonal variables affected productivity, with Top-Phos (R) showing a greater correlation with the yield metrics at greater depths.
Keywords: Fertilisation depth; Natural phosphate; Phosphate fertiliser; Top-Phos; Zea mays L